A study of lip prints among Pondicherry population - G Kumar; N Vezhavendhan; Priya Vendhan (Journal of Forensic Dental Sciences, 2012)
Background: Cheiloscopy is a forensic investigation that deals with the examination of the system of furrows on the red part of human lips. Like fingerprint, lip print is also unique for every individual. But most of the crime-detecting agencies are unaware of the importance of lip print and it is not commonly attempted in identification of the suspects. Aim: The aim of the present study is to determine the predominant lip print pattern among Pondicherry population, India, and also to determine its uniqueness. Materials and Methods: The study comprised of 60 students (30 males and 30 females), aged from 17 to 25 years, from Pondicherry population, India. A dark-colored lipstick was applied with a single stroke and the students were asked to rub both the lips to spread the applied lipstick, after which a lip print was made on butter paper. The lip print was visualized with magnifying lens. Statistical Analysis: Percentage calculation method was used to identify the predominant lip pattern. One-sample T test was done to identify the statistical significance within the different types of lip pattern with P value < 0.05. Results and Conclusion: The present study concludes that every individual has unique lip print and Type III appears to be the most predominant pattern in males, followed by the Type II, Type IV, Type I and Type V patterns. In females, Type II appears to be the most predominant pattern followed by the Type IV, Type I, Type III and Type V patterns.